The effect of COVID-19 on the characteristics of adult emergency department visits: A retrospective cohort tertiary hospital experience in Riyadh - Raied Alotaibi; Ali Alahmari; Ibrahim Ababtain; Abdullah Altamimi; Abdullah Alkhaldi; Mohammed Alhelail; Majid Alsalamah (Elsevier, 2022)
Background: On March 2, 2020, Saudi Arabia identified the first positive COVID-19 case. Since then, several aspects of the COVID-19 impact on Emergency Departments (EDs) use have been reported. The objective of this study is to describe the pattern and characteristics of Emergency Department visits during the COVID-19 pandemic period, compared with the same period in the previous year, including the patients' demographic information, acuity level, length of stay, and admission rate. Methods: Data were collected from King Abdulaziz Medical City in Riyadh, Saudi Arabia. The health records of all the patients who presented at the Emergency Department from January 2019 to September 2020 were retrospectively reviewed. The variations in the patient and the visit characteristics were described for the periods before and during COVID-19. Results: The records of 209,954 patients who presented at the Emergency Department were retrieved. In contrast to 2019, the number of visits during the pandemic period reduced by 23%. A dramatic decrease was observed after the announcement of the first COVID-19 diagnosed case in Saudi Arabia, and subsequently the numbers gradually increased. The patients who presented at the Emergency Department during the pandemic period were slightly older (mean age, 43.1 versus 44.0 years), more likely to be older, more urgent and had a higher admission rate compared to the pre-pandemic period. There was a slight increase in visits during the daytime curfew hours and a decrease during the nighttime. Conclusion: We report a considerable decrease in the number of Emergency Department visits. The reduction was higher in non-urgent and less urgent cases. Patients presenting at the Emergency Department during the curfew times were more likely to stay longer in the Emergency Department and more likely to be admitted, compared with the pre-pandemic period.